2019
DOI: 10.1176/appi.prcp.20180009
|View full text |Cite
|
Sign up to set email alerts
|

World Opioid and Substance Use Epidemic: A Latin American Perspective

Abstract: The opioid crisis is a growing social and public health phenomenon, particularly in developed countries such as the United States. Since the 1990s, this crisis has shown a variety of causal processes and consequences and has affected quality of life for millions of individuals, families, and communities across the globe. Although abuse of opioid‐based painkillers appears to have triggered the epidemic in the United States, in this article, the problem is examined with a focus on Latin America, where drug‐assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The Centers for Disease Control and Prevention (CDC) guidelines recommend the use of non-opioid analgesics for the treatment of chronic pain, saving opioids only for when it is expected that the benefits for pain control and improved function exceed those risks [9]. On the other hand, the perception of health authorities in Latin America is that drug abuse is a growing problem, but the quantity and quality of information is limited [40]. In Colombia, Yucumá et al found a mean rate of 3.9 cases of mental and behavioral disorders due to opioid use per 100,000 inhabitants, with an increase in cases, since it went from 1.6/100,000 inhabitants in 2009 to 5.0/100,000 inhabitants in 2018, with a predominance of males and in the central region of the country [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Centers for Disease Control and Prevention (CDC) guidelines recommend the use of non-opioid analgesics for the treatment of chronic pain, saving opioids only for when it is expected that the benefits for pain control and improved function exceed those risks [9]. On the other hand, the perception of health authorities in Latin America is that drug abuse is a growing problem, but the quantity and quality of information is limited [40]. In Colombia, Yucumá et al found a mean rate of 3.9 cases of mental and behavioral disorders due to opioid use per 100,000 inhabitants, with an increase in cases, since it went from 1.6/100,000 inhabitants in 2009 to 5.0/100,000 inhabitants in 2018, with a predominance of males and in the central region of the country [41].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the perception of health authorities in Latin America is that drug abuse is a growing problem, but the quantity and quality of information is limited [ 40 ]. In Colombia, Yucumá et al found a mean rate of 3.9 cases of mental and behavioral disorders due to opioid use per 100,000 inhabitants, with an increase in cases, since it went from 1.6/100,000 inhabitants in 2009 to 5.0/100,000 inhabitants in 2018, with a predominance of males and in the central region of the country [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…While comparative data are scarce, the context of opioid use and harms in Latin America differs from that in North America [ 21 ]. In Latin America, there are significantly lower amounts of medically prescribed opioids, especially when compared to high-income countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The opioid abuse crisis is a dangerous and growing problem in many parts of the world. [1][2][3] For example, in Brazil, while the drug monitoring program has been successful at keeping opioid prescriptions low, 4 the sales of prescription opioids still increased by more than 450% between 2009 and 2015. 5 The opioid epidemic is especially significant in the United States, where opioid overdose deaths account for more than 60% of all drug overdose deaths.…”
Section: Introductionmentioning
confidence: 99%